SARS-CoV-2 at the human-animal interface: A review. Issue 12 (December 2021) - Farag, Elmoubasher A.; Islam, Md Mazharul; Enan, Khalid; El-Hussein, Abdel-Rahim M.; Bansal, Devendra; Haroun, Mohamed
Abstract: Since its emergence in China in December 2019, COVID-19 remains the recent leading disease of concern drawing the public health attention globally. The disease is known of viral origin and zoonotic nature originating from animals. However, to date neither the source of the spillover nor the intermediate hosts are identified. Moreover, the public health situation is intermittently aggravated by identification of new animals susceptible to the SARS-CoV-2 infection, potentially replicating the virus and maintaining intra and interspecies spread of the disease. Although the role of a given animal and/or its produce is important to map the disease pattern, continuous efforts should be undertaken to further understand the epidemiology of SARS-CoV-2, a vital step to establish effective disease prevention and control strategy. This manuscript attempted to review updates regarding SARS-CoV-2 infection at the human-animal interface with consideration to postulations on the genetic relatedness and origin of the different SARS-CoV-2 variants isolated from different animal species. Also, the review addresses the possible role of different animal species and their produce in transmission of the disease. Also, the manuscript discussed the contamination potential of the virus and its environmental stability. Finally, we reviewed the currently instituted measures to prevent and manage the spread of SARS-CoV-2 infection. The manuscript suggested the One Health based control measures that could prove of value for the near future. Highlights: Eleven animal species over 30 countries naturally contract SARS-CoV-2 infection. Minks establish anthropozoonosis to SARS-COV-2 infection. A lot is behind to reveal about SARS-CoV-2 at the human-animal interface. Abstract : COVID-19, SARS-CoV-2, Human-animal interface, Control.